2019
DOI: 10.3390/pharmaceutics11010030
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Study of the Antibacterial Applications and Oxidative Stress Induction of Copper Maleamate-Functionalized Mesoporous Silica Nanoparticles

Abstract: Mesoporous silica nanoparticles (MSNs) are an interesting class of nanomaterials with potential applications in different therapeutic areas and that have been extensively used as drug carriers in different fields of medicine. The present work is focused on the synthesis of MSNs containing a maleamato ligand (MSN-maleamic) and the subsequent coordination of copper(II) ions (MSN-maleamic-Cu) for the exploration of their potential application as antibacterial agents. The Cu-containing nanomaterials have been char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 68 publications
1
28
2
Order By: Relevance
“…In this context, since 2009 our team has been working on the use of porous silica-based nanostructured materials such as MCM-41, SBA-15, hexagonal mesoporous silica (HMS), MSU-2, KIT-6 or mesoporous silica nanoparticles (MSNs) functionalized with different metallodrugs [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Previous studies have shown that these systems usually work as “non-classical” drug delivery systems, namely, acting as an entire nanoparticulated therapeutic system, without the need of the released metallodrug to be cytotoxic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, since 2009 our team has been working on the use of porous silica-based nanostructured materials such as MCM-41, SBA-15, hexagonal mesoporous silica (HMS), MSU-2, KIT-6 or mesoporous silica nanoparticles (MSNs) functionalized with different metallodrugs [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Previous studies have shown that these systems usually work as “non-classical” drug delivery systems, namely, acting as an entire nanoparticulated therapeutic system, without the need of the released metallodrug to be cytotoxic.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that most of the studied systems do not bear any potential targeting molecule to detect and potentiate the active and selective transport of the therapeutic species to the cancer cell line, an enhanced permeability and retention (EPR) effect was considered to be responsible for their slight selectivity towards cancer cell lines (in comparison with normal cell lines) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Nevertheless, very recent reports have studied the possibility of including a folate fragment for a more effective targeting of cancer cells, which has been partially achieved both in vitro [ 33 ] and in vivo [ 34 ] when using organotin(IV)-functionalized mesoporous silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Gómez‐Ruiz and co‐workers prepared MS NPs containing a maleamato ligand (MS NP‐maleamic) which was used to coordinate copper(II) ions (MS NP‐maleamic‐Cu) and explored their potential application as antibacterial agents against E. coli and S. aureus (see Figure ) . The results showed a low activity of MS NP‐maleamic and MS NP‐maleamic‐Cu against S. aureus , while a good activity against E. coli was found.…”
Section: Ms In Antibacterial Applicationsmentioning
confidence: 99%
“…In recent years, mesoporous silica nanoparticles (MSN) fabricated based on various kinds of templates have aroused a lot of interest owing to their rigid frame, good biocompatibility and biodegradability, unique structural features (tunable mesopores in the range of 2–50 nm, large pore volume as well as total surface area), and facile surface modification [1,2,3,4]. To better play the bio-recognition performance, MSN will be modified by chiral small molecules [5,6,7,8], whereas the chiral mesoporous silica nanoparticles (CMSN) will tend to reduce the mesopores size. Enlarging the mesopores of CMSN can load biomacromolecule and protect its activity [9].…”
Section: Introductionmentioning
confidence: 99%